A Study of Task-Space Path-Velocity Control for Torque-Limited Redundant Manipulators under Uncertainties - Jia, Zheng ; 0000-0001-9193-1676; Karayiannidis, Yiannis ; 0000-0001-5129-342X; Olofsson, Björn (2025 European Control Conference (ECC), 2025)
This paper addresses the time-optimal path-tracking problem for redundant manipulators. By integrating path-velocity control into existing task-space robot controllers, the task-space motion can be dynamically scaled to satisfy the torque constraint under both kinematic and dynamic uncertainties. Numerical simulations and experiments demonstrate that trajectory feasibility and path-tracking accuracy of the task-space controllers can be significantly improved by integrating path-velocity control. In addition, the nullspace motion of redundant manipulators can be exploited to further improve the performance by tracking the approximate time-optimal joint trajectory associated with the tasks in nullspace.
Keywords: Uncertainty; Torque; Accuracy; Tracking; Dynamics; Europe; Kinematics; Numerical simulation; Trajectory; Manipulator dynamics